Management Control System and Performance: Accountability Attributes in Local Authorities - Ilias, Norazlina; Abdulatiff, Nik Kamaruzaman; Mohamed, Nafsiah (International Journal of Economics and Financial Issues, 2016)
This study used the structural equation modeling (SEM) tool to examine the impact of MCS on performance in Malaysian local authorities. This study applies a questionnaire-based survey to look for responses from 899 heads of departments attached to the local authorities within Peninsular Malaysia. Out of the 899 questionnaires distributed, 372 were returned, which resulted in 335 usable responses that were used for further analysis. Statistical results showed that the external control and formal internal control were significantly associated with all three performance dimensions – financial, service quality, and procedural, as expected. However, the internal informal control only had a significant relationship with the service quality performance. This study also revealed that the external control, through the presence of the formal internal control, had a stronger relationship with all the three performance dimensions, as compared to the direct relationship between the external control and performance. Keywords: MCS, Performance, Accountability, Local authorities, Structural Equation Modeling JEL Classifications: M410, M490